Al-Quran Recitation Therapy with Surah Ar-Rahman on Students' Sleep Quality: A Randomized Controlled Trial - Nurlela, Lantu; Asih, Fujiasih; Pindi, Kurniawati; Syamsuriati, Syamsuriati (Diversity: Disease Preventive of Research Integrity, 2024)
Sleep quality is the level of sleep satisfaction experienced by a person which includes the components of sleep quantity, sleep continuity, and fresh and fit when waking up. Poor sleep quality is associated with psychiatric disorders, such as depression and anxiety. Recitation (Murottal) Al- Quran Surah Ar-Rahman Therapy is the chanting of the holy verses of Al-Quran Surah Ar-Rahman which is given to someone to have a relaxing effect. The research was conducted on students using the randomized control trial experimental research method with pre and post approaches with the control group. The study was conducted on 36 respondents (18 respondents in the intervention group and 18 respondents in the control group). The results showed that there was an increase in sleep quality by 13.2% in the intervention group after therapy. The mean difference in sleep quality which showed an increase in sleep quality was 0.11 greater in the intervention group than the control group, but not significant (p=0.908, α=0.05). There was an increase in sleep quality for students after being given Murottal Al Quran Surah Ar-Rahman therapy. Further research is needed with a longer treatment time and it is necessary to study the factors that most influence the sleep quality of master students.